Handbook of instrumentation and controls - Kallen, Howard P. (McGraw-Hill Handbooks, 1961)
Introduction - Instrumentation and control fundamentals - Measurement of pressure and draft - Temperature measurement - Measurement of flow - Measurement and control of liquid level - Final control elements - Measurement and control of ph and conductivity - Boiler instrumentation and control systems - Steam-pressure reducing and desuperheating - Steam-turbine instrumentation and control - Diesel-engine governing - Control of heating, air-condition-ing, and refrigeration systems.